TEACHING INTERNET SLUNG IN ESP CLASS - Azizova Makhsuda Ahmadaliyevna (Bright Mind Publishing, 2025)
In the digital age, the integration of internet slang into English for Specific Purposes (ESP) classrooms has become increasingly relevant. This article explores the implications and methodologies for teaching internet slang within ESP curricula, focusing on its role in fostering effective communication skills among learners in various professional contexts. By analyzing the linguistic features of internet slang and its pervasive influence on contemporary discourse, we highlight the need for educators to address this evolving language form. Through a series of pedagogical strategies, including interactive activities, contextualized learning scenarios, and collaborative projects, we demonstrate how incorporating internet slang can enhance learners' engagement and cultural competence. Furthermore, we discuss potential challenges and considerations for educators when integrating this informal language into structured learning environments. Ultimately, this article advocates for a balanced approach that embraces linguistic innovation while reinforcing formal language standards in ESP education.
Keywords: Internet slang, English for Specific Purposes (ESP), digital communication, pedagogy, linguistic innovation.